Making the Invisible Visible: Magnetic Fields in Accretion Flows Revealed by X-Ray Polarization - Samuel Barnier; Chris Done (The Astrophysical Journal)
Large-scale, strong magnetic fields are often evoked in black hole accretion flows, for jet launching in the low/hard state and to circumvent the thermal instability in the high/soft state. Here, we show how these ideas are strongly challenged by X-ray polarization measurements from the Imaging X-ray Polarimetry Explorer (IXPE). Quite general arguments show that equipartition large-scale fields in the accretion flow should be of order 10 ^6–8 G. These produce substantial Faraday rotation and/or depolarization. Since IXPE observes polarization in both spectral states, this sets upper limits to coherent large-scale (vertical, radial, or azimuthal) magnetic fields in the photosphere of B ≲ 5 × 10 ^6 G. While we stress that Faraday rotation should be calculated for each individual simulation (density, field geometry, and emissivity), it seems most likely that there are no equipartition-strength large-scale ordered fields inside the photosphere of the X-ray-emitting gas. Strong poloidal fields can still power a Blandford–Znajek jet in the low/hard state if they thread the black hole horizon rather than the X-ray-emitting flow, but this could also be challenged by (lack of) depolarization from vacuum birefringence. Instead, an alternative solution is that the low/hard state jet is dominated by pairs, so can be accelerated by lower fields. Strong toroidal fields could still stabilize the disk in the high/soft state if they are buried beneath the photosphere, though this seems unlikely due to magnetic buoyancy. Fundamentally, polarization data from IXPE mean that magnetic fields in black hole accretion flows are no longer invisible and unconstrained.